CO-Releasing Molecule (CORM)-3 Ameliorates Spinal Cord-Blood Barrier Disruption Following Injury to the Spinal Cord - Zheng, Gang; Zheng, Fanghong; Luo, Zucheng; Ma, Haiwei; Zheng, Dongdong; Xiang, Guangheng; Xu, Cong; Zhou, Yifei; Wu, Yaosen; Tian, Naifeng; Wu, Yan; Zhang, Tan; et al. (Frontiers in Pharmacology, 2020)
Spinal cord injury (SCI) is a clinical tough neurological problem without efficient cure currently. Blood-spinal cord barrier (BSCB) interruption is not only a crucial pathological feature for SCI process but is a possible target for future SCI treatments; however, few treatments have been developed to intervene BSCB. In the present study, we intravenously injected CO-releasing molecule3 (CORM-3), a classical exogenous CO donor, to the rats experiencing SCI and assessed its protection on BSCB integrity in rats. Our results demonstrated that the exogenous increasing of CO by CORM-3 blocked the tight junction (TJ) protein degeneration and neutrophils infiltration, subsequently suppressed the BSCB damage and improved the motor recovery after SCI. And we certified that the CO-induced down-regulation of MMP-9 expression and activity in neutrophil might be associated with the NF-κB signaling. Taken together, our study indicates that CO-releasing molecule (CORM)-3 ameliorates BSCB after spinal cord injury.